2012
DOI: 10.1016/s1672-0229(11)60032-6
|View full text |Cite
|
Sign up to set email alerts
|

SMS 2.0: An Updated Database to Study the Structural Plasticity of Short Peptide Fragments in Non-Redundant Proteins

Abstract: The function of a protein molecule is greatly influenced by its three-dimensional (3D) structure and therefore structure prediction will help identify its biological function. We have updated Sequence, Motif and Structure (SMS), the database of structurally rigid peptide fragments, by combining amino acid sequences and the corresponding 3D atomic coordinates of non-redundant (25%) and redundant (90%) protein chains available in the Protein Data Bank (PDB). SMS 2.0 provides information pertaining to the peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In recent years, several methods based on similarity and dissimilarity comparison have advanced rapidly to understand the structure, function and property of proteins [25–28] paving the way to the design of novel proteins. For example, Alexander et al [29] designed two proteins with identical sequence apart from one residue mismatch and found that these two proteins adopt completely different folds and functions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several methods based on similarity and dissimilarity comparison have advanced rapidly to understand the structure, function and property of proteins [25–28] paving the way to the design of novel proteins. For example, Alexander et al [29] designed two proteins with identical sequence apart from one residue mismatch and found that these two proteins adopt completely different folds and functions.…”
Section: Discussionmentioning
confidence: 99%
“…The ProtParam tool of ExPASy [7] was used to record the physicochemical characterization of proteins, including the amino acid sequence composition, instability index, aliphatic index, and GRAVY. Using SMS (v.2.0) [8], the theoretical isoelectric point (pI) and GRAVITY of the SSI32830.1 protein were also determined.…”
Section: Characterization Of the Selected Protein's Physicochemical P...mentioning
confidence: 99%
“…The domain that appears in identical protein sequences is identified by the NCBI CDD tool. When comparing a test sequence to position-specific rating datasets derived from conserved domain (CD) alignments in the CD protein cluster, CD-Search utilizes RPS-BLAST (8,29). The CD search engine discovered a conserved domain in the protein SSI32830.1 (30-32).…”
Section: Functional Annotation Of the Selected Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, as a result of advances in datacollection technology and various ambitious structural genomics initiatives, numerous macromolecular crystal structures have been X-ray analysed and deposited in the Protein Data Bank (PDB) (Berman et al, 2000;Balamurugan et al, 2007). The sequence and three-dimensional structure of a protein molecule contains crucial information defining its structure and function (Samaya Mohan et al, 2005;Balamurugan et al, 2005Balamurugan et al, , 2006Gopalakrishnan et al, 2007;Ravella et al, 2012). The primary sequence of a protein is determined by various known sequencing techniques and the three-dimensional structure is resolved by biophysical techniques such as X-ray crystallography, NMR etc.…”
Section: Introductionmentioning
confidence: 99%